2009
DOI: 10.1063/1.3155999
|View full text |Cite
|
Sign up to set email alerts
|

Particle shape effects on thermophysical properties of alumina nanofluids

Abstract: Effect of temperature on turbulent and laminar flow efficacy analysis of nanofluids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
363
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 801 publications
(395 citation statements)
references
References 30 publications
26
363
2
4
Order By: Relevance
“…[38][39][40][41] powerlaw distance-decaying functions have been chosen, resulting in a fractional-order heat conduction equation with some specific fractional operators [38][39][40][41]. Results have been found in agreement with non-classical thermodynamic behavior observed, for instance, in micro-and nano-devices [42][43][44].…”
Section: Introductionsupporting
confidence: 61%
“…[38][39][40][41] powerlaw distance-decaying functions have been chosen, resulting in a fractional-order heat conduction equation with some specific fractional operators [38][39][40][41]. Results have been found in agreement with non-classical thermodynamic behavior observed, for instance, in micro-and nano-devices [42][43][44].…”
Section: Introductionsupporting
confidence: 61%
“…There are very few results available in the literature about the effect of particle shape on the viscosity of nanofluids [38,39]. However, viscosity has strong dependence on the particle shape.…”
Section: Effect Of Particle Size and Shapementioning
confidence: 98%
“…However, viscosity has strong dependence on the particle shape. Timofeeva et al [39] reported that elongated particles increase the viscosity of nanofluids rather than spherical nanoparticles. Ferrouillat et al [40] presented another interesting study on the influence of nanoparticle shape factor on convective heat transfer and performance of water-based SiO 2 and ZnO nanofluids.…”
Section: Effect Of Particle Size and Shapementioning
confidence: 99%
“…Timofeeva et al [65] found that the thermal conductivity was not significantly affected by aggregation, whereas, Wamkam et al [65,66] observed a significant enhancement of thermal conductivities (>20%) in 3 wt % suspensions when aggregation was most pronounced. Both groups suggest that the reason for the discrepancy lies in the nature and amount of the agglomeration: strong aggregates, which could lead to k eff enhancement; and aggregate-like ensembles, which occur due to weak repulsive forces between particles and are unlikely to enhance k eff because of the solidliquid-solid interfacial resistance.…”
Section: 1 1 T H E R M a L C O N D U C T I V I T Ymentioning
confidence: 99%